Strengthening Ecological Citizenship to Realize Environmental Resilience through the Waste Bank Movement - Rd Sugara Mochamnad Haddad; Fenty Putri Rahayu (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this study is to analyze the strengthening of ecological citizenship to realize environmental resilience through the waste bank movement in Sukamulya Village RT 11 RW 04 Dawuan Kaler. This research uses a qualitative approach with a case study design. The population in this study was the community of RT 11 RW 04 Sukamulya Village with 15 respondents. Data collection using observation, interview, and documentation techniques. Data analysis uses interactive analysis techniques consisting of data reduction, data presentation, and data verification. The results showed that strengthening ecological citizenship to realize environmental resilience consists of: independent waste management, planting trees, and establishing a waste bank movement. The results of ecological citizenship as a form of environmental resilience have a positive impact on several fields, namely: environmental, social, and economic. The challenges and obstacles in the development of Sukamulya Village lie in the concern of the community who sometimes go up and down and the elderly who are still unfamiliar with environmental resilience. Synergy between the community and the government must be open and interactive in realizing environmental resilience in Sukamulya Village